Multicomponent wound dressing - Padrão, Jorge (2021)
This works describes the antimicrobial (antibacterial and antiviral) performance of a multicomponent fabric for wound dressing. The fabric comprises a scaffold of plasma activated polyester (PES), enveloped in a matrix of chitosan (CH) containing silver nanoparticles (AgNPs) and the zeolite mordenite (MOR). The antimicrobial efficacy of the cumulative addition of each of these components was evaluated.